El examen del CAD y la cooperación española - Tejada Chacón, Luis (Revista Española de Desarrollo y Cooperación, 2023)
The OECD’s Development Assistance Committee regularly makes “peer reviews” of its members’ co-operation policies. Spain’s third exam took place this year, during which the examiners underlined some accomplishments, such as the adoption of the Co-operation Act or the Master Plan 2001-2004, or its experience and advantage in institutional support, but made several recommendations to improve the quality of Spanish Co-operation. They agreed that, even working mostly in countries with middle income countries, Spain should focus in poverty reduction. It is also recommended to improve the co-ordination between different spanish official donors, and increase the resources up to 0,33% of GNP from here to 2006.